Polycarpon tetraphyllum (Caryophyllaceae) a new record for the Colombian flora and a key to the genera of the Caryophyllaceae from Colombia - Fonseca-Cortés, Andrés; Sandoval-Ortega, Manuel Higinio (Phytotaxa, 2022)
Polycarpon tetraphyllum subsp. tetraphyllum, a species mostly occuring naturally in the Mediterranean region, is recorded for the first time for the Colombian flora. This species is easily recognized by its scarious stipules, flowers with five keeled sepals with scarious margins, three white petaloid staminodes, and D-shaped papillated seeds. To the date, this species only has been recorded in Bogotá D.C., growing through the pavement. Additionally, we present the first key to genera of the Caryophyllaceae present in Colombia.